Sulfamethoxazole and ciprofloxacin removal using a horizontal-flow anaerobic immobilized biomass reactor - Chatila, Sami; Amparo, Maura R.; Carvalho, Lucas S.; Penteado, Eduardo D.; Tomita, Inês N.; Santos-Neto, Álvaro J.; Gomes, Paulo C. F. Lima; Zaiat, Marcelo (Environmental Technology, 2015)
The antibiotics sulfamethoxazole (SMTX) and ciprofloxacin (CIP) are commonly used in human and veterinary medicine, which explains their occurrence in wastewater. Anaerobic reactors are low-cost, simple and suitable technology to wastewater treatment, but there is a lack of studies related to the removal efficiency of antibiotics. To overcome this knowledge gap, the objective of this study was to evaluate the removal kinetics of SMTX and CIP using a horizontal-flow anaerobic immobilized biomass reactor. Two different concentrations were evaluated, for SMTX 20 and 40 μg L(-1); for CIP 2.0 and 5.0 μg L(-1). The affluent and effluent analysis was carried out in liquid chromatography/tandem mass spectrometry (LC-MS/MS) with the sample preparation procedure using an off-line solid-phase extraction. This method was developed, validated and successfully applied for monitoring the affluent and effluent samples. The removal efficiency found for both antibiotics at the two concentrations studied was 97%. Chemical oxygen demand (COD) exhibited kinetic constants that were different from that observed for the antibiotics, indicating the absence of co-metabolism. Also, though the antibiotic concentration was increased, there was no inhibitory effect in the removal of COD and antibiotics.
Keywords: Lc-ms/ms analysis; Sulfamethoxazole; Ciprofloxacin; Horizontal-flow anaerobic immobilized biomass reactor; Removal kinetics